2002
DOI: 10.1007/s00167-001-0274-7
|View full text |Cite
|
Sign up to set email alerts
|

The tibial attachment of the anterior cruciate ligament in children and adolescents: analysis of magnetic resonance imaging

Abstract: Recent studies have demonstrated that skeletally immature athletes with an ACL injury may require surgical reconstruction if they return to high-demand sports. This study used MRI to compare the anatomy of the ACL in skeletally immature and adult subjects. Measurements were recorded in the sagittal plane for the anterior-posterior dimension of the proximal tibia, and the anterior, center, and posterior limits of the ACL, and the roof inclination angle of the femur. These values were compared to established ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Therefore, the purpose of this cross-sectional study was to characterize anatomic parameters of the ACL tibial insertion and proximal tibial epiphysis at MRI in a large population of skeletally immature knees to provide normative data to assist surgeons in planning anatomic and/or physealsparing ACL reconstruction. We hypothesized that the center of the ACL tibial attachment would be located at~44% of the tibial anteroposterior diameter (APD), consistent with a prior pilot study, 24 and that, when normalized to overall knee size, would vary little by age or sex.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, the purpose of this cross-sectional study was to characterize anatomic parameters of the ACL tibial insertion and proximal tibial epiphysis at MRI in a large population of skeletally immature knees to provide normative data to assist surgeons in planning anatomic and/or physealsparing ACL reconstruction. We hypothesized that the center of the ACL tibial attachment would be located at~44% of the tibial anteroposterior diameter (APD), consistent with a prior pilot study, 24 and that, when normalized to overall knee size, would vary little by age or sex.…”
Section: Discussionmentioning
confidence: 87%
“…14 Shea et al used MRI to define the anterior, central, and posterior position of the ACL tibial attachment in skeletally immature patients but in only 22 knees. 24 A larger, population-based MRI study in this age group would provide a more comprehensive reference for planning primary and revision ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the pediatric literature has particularly focused on MRI characteristics of the ACL and the epiphyseal dimensions [18][19][20][21]. These studies have aimed to further characterize pediatric knee anatomy to determine optimal surgical candidates and techniques for safe ACL reconstruction in skeletally immature patients.…”
Section: Acl and Physeal Anatomymentioning
confidence: 99%
“…96 Several investigations have documented that pediatric knees have more ligamentous laxity than adult knees. 8,33,34,47 Additionally, Behr et al 9 and Shea et al 94 have described the anatomy of the ACL in skeletally immature individuals and shown that the femoral origin is completely epiphyseal, which makes the drilling of graft tunnels a technical challenge for orthopaedic surgeons. However, the femoral and tibial insertion sites in children of all ages, regardless of skeletal maturity, have proven to be consistently similar to adult insertion sites.…”
Section: The Anterior Cruciate Ligament and The Skeletally Immature Kneementioning
confidence: 99%